In it for the Long Haul Coaching is Key to Continued Development - Hernez-Broome, Gina; Hernez-Broome, Gina (Center for Creative Leadership, 2002)
So you've gone through a weeklong leadership development program, and now you're back in the real world of work. Will you be able to sustain the learning process that began in the program and effect substantive behavioral change, or will the energy created during the program evaporate over time? Evidence shows that one way to help ensure the former result is to engage in follow-up coaching.